Republic of Poland : Selected Issues. (IMF Staff Country Reports; Country Report ;, 2006)
This paper provides evidence that globalization has dampened inflation in Poland in the last ten years. A broad-based statistical and econometric analysis of financial and household balance sheet data implies that exchange rate-related credit risk and liquidity risk are currently contained. Rapid growth of foreign currency loans puts a premium on sound lending practices, risk management, and effective supervision. The many indicators examined in this paper suggest that there exists considerable room for enhancing the flexibility of the Polish economy.